Penguatan Teknologi Olah Buah Salak dalam Upaya Peningkatan Kualitas Produk - Juwitaningtyas, Titisari; Astuti, Erna; Tarmuji, Ali (Berdikari: Jurnal Inovasi dan Penerapan Ipteks, 2020)
Salak pondoh is a typical fruit of Sleman Regency which has been known domestically and abroad. Salak pondoh fruit has been generally marketed in fresh and processed form. The Agawe Santosa Community Association (MAS) located in Turi District, Sleman is one of the Micro, Small and Medium Enterprises (MSMEs) that produces various processed salak fruit. The availability of the fresh fruit as raw material for processing salak fruit has fluctuated due to the season, so the volume of processed salak fruit products also becomes unstable. This condition gets even worse because of the fruit processing technology which is still conventional. Efforts to maintain volume stability of salak fruit processed products need to be done so that fluctuations in producer income can be reduced. Community empowerment program or UMKM through strengthening the technology of salak fruit is a solution to maintain this stability. The empowerment of salak fruit processing technology is through the application of Vacuum Frying Technology (low pressure vacuum frying). This technology is able to guarantee that salak fruit processed products can be stored for a relatively long time. The application of Vacuum Frying technology is carried out in several stages, which are introduction, education (training and technology transfer practices), mentoring, and post-practice monitoring of technology application so that sustainability is guaranteed. Empowerment of UMKM Paguyuban MAS is said to be successful with indicators of increasing knowledge and skills in using Vacuum Frying (especially chips products) by 58.4%, packaging processed salak fruit products (chips) and production management by 60%, as well as guaranteeing business sustainability.